HUBUNGAN HARGA KOPRA TERHADAP TINGKAT PRODUKSI KOPRA DI KABUPATEN MINAHASA SELATAN - Ayu L. Rusno; Olly E. H. Laoh; Welson M. Wangke; Ellen G. Tangkere (COCOS, 2014)
ABSTRACTFluctuations in the price of copra became a significant problem among farmers where if prices fluctuate often farmers will be disadvantaged as a result of sales sometimes do not cover production costs. The objective of this study is to determine there is a relation between the price of copra toward the production level in South Minahasa Regency.This study is conducted in Southern Minahasa Regencywhere the data is collected from Central Statistics Agency of Southern Minahasa, and Plantation Service of Southern Minahasa Regency. Then the data is analyzed by using descriptive analysis.The research result showed that the price could be used as basic for the farmers of the in increasingthe production of copra in South Minahasa Regency. There is no relation between the price of copra and its production in South Minahasa Regency, and also it could be said that the price fluctuations had not been able to make the farmers improve the productivity level.